Preparation of oxygen-doped modified three-dimensional porous carbon and its application in deep treatment of phenolic organic wastewater

By modifying three-dimensional porous carbon as an anode catalyst, the energy consumption and catalyst deactivation problems in the existing technology under high temperature and high pressure conditions are solved, and the deep oxidation and degradation of phenolic organic pollutants under normal temperature and pressure are achieved, and secondary pollution is avoided.

CN116281944BActive Publication Date: 2025-03-18HEFEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310310049.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-03-18
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

The prior art requires high temperature and high pressure conditions when dealing with phenolic organic pollutants, resulting in large energy consumption and catalyst deactivation, and traditional catalysts have the risk of secondary pollution.

Method used

The oxygen-doped modified three-dimensional porous carbon is used as the anode catalyst. Through the combined treatment process of chemical oxidation, hydrothermal reaction and electrochemical activation, the doping amount of carbonyl functional groups is increased, and the deep oxidation and degradation of phenolic organic pollutants under normal temperature and pressure are achieved.

Benefits of technology

Complete degradation of phenolic organic pollutants is achieved, and the catalyst is stable and has no metal ion leaching, avoiding secondary pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116281944B_ABST
    Figure CN116281944B_ABST
Patent Text Reader

Abstract

The invention discloses the preparation of oxygen-doped modified three-dimensional porous carbon and its application in deep treatment of phenolic organic wastewater. First, the surface of graphitized three-dimensional porous carbon is oxidized by using piranha etching solution as an oxidant, and then the surface is subjected to hydrothermal reaction at a certain temperature to remove unstable oxygen-containing functional groups, and finally the surface is placed in H2SO4 solution for electrochemical activation to obtain oxygen-doped modified three-dimensional porous carbon material. Under normal temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon is used as an anode catalyst, a graphite plate is used as a cathode, and Na2SO4 is used as an electrolyte. Under certain pH conditions, at a current density of 1 mA cm ‑2 The catalytic air oxidation driven by the weak electric field can completely remove low concentration phenolic organic matter in the wastewater within 2 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a doping modification of a carbon material and an application thereof in catalytic oxidation, in particular to the preparation of oxygen-doped modified three-dimensional porous carbon and an application thereof in deep treatment of phenolic organic wastewater. Background Art

[0002] With the development of industrial production, the number and types of phenolic organic pollutants in industrial wastewater from industries such as plastics, dyeing, and pulp are also increasing rapidly. Phenolic pollutant wastewater is widely distributed in various water bodies, and even at low concentrations, it is highly toxic to humans and organisms. In addition, the physical and chemical properties of phenolic pollutants are stable and can exist in water bodies for a long time. It is reported that the concentration of phenolic pollutants is 1 to 2 mg·L -1 It is harmful to fish when the concentration reaches 10-100 mg / L -1 The toxicity to aquatic organisms and humans is greatly increased (Zhou et al. J. Langmuir. 2019, 35, 12914-12926.). The traditional treatment methods for phenolic organic pollutants mainly include biodegradation, physical adsorption and chemical oxidation. Biological treatment has specificity, but it is time-consuming to cultivate biological strains, and it is easily inactivated in phenol-containing toxic wastewater, resulting in low treatment efficiency (Zheng et al. J. Environ. Pollut. 2018, 238, 783-791.). Although physical adsorbents can quickly reduce the concentration of phenolic pollutants, the regeneration cost of the adsorbent is expensive and the adsorbed residues are prone to secondary pollution (Yuan et al. J. Environ. Pollut. 2020, 262, 114172.). Therefore, seeking a green, efficient and low-energy chemical oxidation method to completely oxidize and degrade organic pollutants such as phenols or convert them into biodegradable low-toxic substances will be the main research direction in this field.

[0003] Wet air oxidation (WAO) is an efficient advanced oxidation technology. It has received widespread attention because it uses green, environmentally friendly, cheap and easily available oxygen as an oxidant and can effectively treat various organic pollutants in wastewater (Kim & Ihm, J. Hazard. Mater. 2011, 186, 16-34). The bottleneck of this technology is that high temperature (200-325°C) and high pressure (5-20MPa) conditions are required to drive the oxidation reaction (Sushuma et al., J. Environmental. Management. 2018, 228, 169-188). These harsh conditions not only cause a large energy consumption, but also have high requirements for reaction equipment. Suitable catalysts can reduce the temperature and pressure of the WAO reaction to a certain extent. For this reason, people have developed a variety of metal-based catalysts for homogeneous and heterogeneous catalytic WAO reaction systems. However, the catalytic WAO reaction reported so far usually still needs to be carried out at relatively high temperature (above 80°C) and pressure (above 0.5 MPa) (Zhang et al., Sci. Rep. 2014, 4, 6797). Such high temperature and high pressure operating conditions are prone to cause catalyst sintering or metal ion leaching for metal or metal oxide catalysts, thereby causing catalyst deactivation or secondary pollution problems (Keav et al., Catal. Sci. Technol. 2011, 1, 342-353).

[0004] Carbon materials have gradually become alternative materials for metal-based catalysts due to their advantages such as low cost, easy availability, environmental friendliness, high conductivity, relatively stable chemical properties, and controllable structure at the atomic level. On the one hand, the good mobility of π electrons in the unique C=C double bond of carbon materials enables them to act as electron transfer media in redox reactions. On the other hand, acidic or alkaline oxygen-containing surface functional groups are easily formed at the defects on the carbon surface, which can provide catalytic active sites for redox reactions. Summary of the invention

[0005] The present invention aims to provide a method for preparing oxygen-doped modified three-dimensional porous carbon and its application in deep treatment of phenolic organic wastewater. The present invention uses commercial graphitized polyacrylonitrile-based three-dimensional porous carbon as a substrate, adopts a simple chemical oxidation, hydrothermal reaction and electrochemical activation combined treatment process, effectively increases the doping amount of carbonyl functional groups on the carbon surface, and uses the prepared oxygen-doped modified three-dimensional porous carbon as an anode catalyst, which can achieve deep oxidation degradation of phenolic organic pollutants in wastewater at room temperature and pressure under the drive of a weak external electric field.

[0006] The preparation method of oxygen-doped modified three-dimensional porous carbon of the present invention comprises the following steps: firstly, using piranha etching solution as an oxidant to oxidize the surface of graphitized three-dimensional porous carbon, then subjecting it to a hydrothermal reaction at a certain temperature to remove unstable oxygen-containing functional groups on the surface, and finally subjecting it to H2 SO 4 Electrochemical activation is carried out in the solution to obtain oxygen-doped modified three-dimensional porous carbon materials.

[0007] The graphitized three-dimensional porous carbon is a commercial graphitized polyacrylonitrile-based three-dimensional porous carbon with a bottom area of ​​1.0 cm 2 , a cubic column 8 cm high, with a pore volume of 7.5 cm 3 ·g -1 The graphitized three-dimensional porous carbon was pretreated before use, specifically, ultrasonically cleaned with acetone and ethanol, respectively, and then immersed in 2 mol·L -1 Soak in NaOH solution at 60℃ for 12h.

[0008] During the oxidation treatment, the amount of the piranha etching solution used is 20 to 50 times the mass of the graphitized three-dimensional porous carbon, and the immersion oxidation time is 4 to 14 hours.

[0009] The reaction temperature of the hydrothermal reaction is 140-220° C., and the reaction time is 6-18 hours.

[0010] The electrochemical activation adopts cyclic voltammetry scanning method, adopts a three-electrode system, uses the carbon material after hydrothermal treatment as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum wire as the counter electrode. The scanning range is between 0 and 1.8 V, and the scanning times are 2 to 8 times; the H 2 SO 4 The mass fraction of the solution is 5 to 20 wt%.

[0011] The application of the oxygen-doped modified three-dimensional porous carbon of the present invention is to use the oxygen-doped modified three-dimensional porous carbon as an anode catalyst to catalyze air oxidation and degradation of phenolic organic pollutants in wastewater.

[0012] Specifically:

[0013] At room temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon was used as the anode catalyst and the graphite plate was used as the cathode. -1 Na 2 SO 4 The electrolyte is the air flow rate of 5L·h -1 , at a current density of 1 mA cm -2 Driven by external direct current, the air can catalyze the oxidation of organic pollutants in wastewater under certain pH conditions, and low-concentration phenolic organic matter in the wastewater can be completely removed within 2 hours.

[0014] The cathode material has a size of 8×1×0.2 cm 3 Rectangular graphite plate.

[0015] The phenolic organic pollutant is a mixture of one or more of bisphenol A, 4-chlorophenol, phenol, and p-methoxyphenol, and the concentration of the phenolic organic pollutant is 5 to 20 mg·L -1 .

[0016] The pH value of the solution is adjusted to be in the range of 5 to 11, preferably 7 to 11.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0018] 1. The present invention uses commercial graphitized three-dimensional porous carbon as a substrate, and after being treated with piranha etching solution oxidation, hydrothermal reaction and electrochemical activation, the proportion of carbonyl functional groups in oxygen-containing functional groups is effectively increased.

[0019] 2. The oxygen-doped three-dimensional porous carbon catalyst obtained by the present invention has high catalytic activity for oxygen under the drive of a weak external electric field, can completely degrade low-concentration phenolic organic pollutants, and the carbon anode catalyst has good stability.

[0020] 3. The present invention uses oxygen-doped modified carbon catalyst as the anode material, which is not only cheap and readily available, but also free of metal ion leaching, thus avoiding secondary pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XPS total spectrum of oxygen-doped modified three-dimensional porous carbon (PGC) obtained by the combined treatment of commercial graphitized polyacrylonitrile-based three-dimensional porous carbon (PGC) with piranha etching solution oxidation (OPGC), hydrothermal reaction (HPGC), and electroactivation (EPGC) in Example 1. It can be seen that the oxygen doping amounts after treatment at different stages are 10.65%, 8.15%, and 11.42%, respectively;

[0022] Figure 2 The C1s and O1s high-resolution XPS spectra of OPGC in Example 1, wherein the percentages of C=O are 14.4% and 40%, respectively;

[0023] Figure 3 The C1s and O1s high-resolution XPS spectra of HPGC in Example 1, wherein the percentages of C=O are 14.2% and 45.5%, respectively;

[0024] Figure 4 The C1s and O1s high-resolution XPS spectra of EPGC in Example 1, wherein the percentages of C=O are 19.7% and 52.9%, respectively;

[0025] Figure 5The catalytic activities of three-dimensional porous carbon OPGC, HPGC and EPGC with different modification degrees in Example 1 are compared. Compared with untreated PGC, the catalytic activity of PGC after oxygen doping modification is significantly improved. It can be seen that with the increase of oxygen doping degree and the increase of C=O content, the catalytic activity of the anode catalyst shows an increasing trend.

[0026] Figure 6 The degradation efficiency of oxygen-doped modified three-dimensional porous carbon anode catalysts prepared in Examples 1 to 4 in catalyzing air oxidation degradation of different phenolic organic pollutants. It can be seen that the removal rates of phenolic organic pollutants with different structures within 2 hours all reached 100%.

[0027] Figure 7 This is the effect of the number of cycles on the catalytic performance of the oxygen-doped modified three-dimensional porous carbon anode catalyst in catalytic air oxidation degradation of bisphenol A in Example 1. It can be seen that the degradation performance of the anode catalyst material has not been significantly reduced after 6 cycles of use.

[0028] Figure 8 The effect of different piranha etching solutions on the catalytic performance of oxygen-doped modified three-dimensional porous carbon anode catalyst under the conditions of Example 1. It can be seen that the optimal time for piranha etching solution oxidation treatment is 10 hours.

[0029] Fig. 9 The effect of different hydrothermal treatment temperatures on the catalytic performance of oxygen-doped modified three-dimensional porous carbon anode catalyst under the conditions of Example 1. It can be seen that the optimal hydrothermal treatment temperature is 180°C.

[0030] Fig.10 The effect of different pH environments on the catalytic performance of oxygen-doped modified three-dimensional porous carbon anode catalyst under the conditions of Example 1. It can be seen that neutral or alkaline conditions are more suitable for oxygen-doped modified three-dimensional porous carbon materials to catalyze the degradation of organic pollutants by air oxidation. DETAILED DESCRIPTION

[0031] The following describes the implementation of the present invention in detail in combination with some technical solutions:

[0032] Embodiment 1:

[0033] 2.0 g of the pretreated PGC was immersed in 100.0 g of piranha etching solution, sealed and placed in a shaker for oxidation treatment for 14 h, and then taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain OPGC; OPGC was transferred to a hydrothermal reactor and completely immersed in water. After reacting at 180 ° C for 12 h, the carbon material was taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain HPGC; finally, in a three-electrode system with HPGC as the working electrode, saturated calomel electrode as the reference electrode, and platinum wire as the counter electrode, 10 wt% H2 SO 4 The solution was used as electrolyte, the scanning speed was 5 mV / s, and cyclic voltammetry scanning was performed 4 times in the range of 0 to 1.8 V. The working electrode was taken out, washed with pure water, and dried to obtain oxygen-doped three-dimensional porous carbon EPGC.

[0034] At room temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon was used as the anode catalyst and the graphite plate was used as the cathode. -1 Na 2 SO 4 The electrolyte is the air flow rate of 5L·h -1 , at a current density of 1 mA cm -2 Driven by a weak electric field, the catalytic oxidation of 1.0L of air containing 10mg·L -1 The degradation rate of bisphenol A reached 100% within 2 hours.

[0035] Embodiment 2:

[0036] 2.0 g of the pretreated PGC was immersed in 80.0 g of piranha etching solution, sealed and placed in a shaker for oxidation treatment for 10 h, and then taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain OPGC; OPGC was transferred to a hydrothermal reactor and completely immersed in water. After reacting at 220 ° C for 6 h, the carbon material was taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain HPGC; finally, in a three-electrode system with HPGC as the working electrode, saturated calomel electrode as the reference electrode, and platinum wire as the counter electrode, 20 wt% H 2 SO 4 The solution was used as electrolyte, the scanning speed was 5 mV / s, and cyclic voltammetry scanning was performed twice in the range of 0 to 1.8 V. The working electrode was taken out, washed with pure water, and dried to obtain oxygen-doped three-dimensional porous carbon EPGC.

[0037] At room temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon was used as the anode catalyst and the graphite plate was used as the cathode. -1 Na 2 SO 4 The electrolyte is the air flow rate of 5L·h -1 , at a current density of 1 mA cm -2 Under the weak electric field of , the catalytic oxidation of 1.0L of air containing 10mg·L -1 The degradation rate of 4-chlorophenol in simulated organic wastewater reached 100% within 2 hours.

[0038] Embodiment 3:

[0039] 2.0 g of the pretreated PGC was immersed in 40.0 g of piranha etching solution, sealed and placed in a shaker for oxidation treatment for 14 h, and then taken out and washed three times with deionized water and anhydrous ethanol to obtain OPGC; OPGC was transferred to a hydrothermal reactor and completely immersed in water. After reacting at 140 ° C for 18 h, the carbon material was taken out and washed three times with deionized water and anhydrous ethanol to obtain HPGC; finally, in a three-electrode system with HPGC as the working electrode, saturated calomel electrode as the reference electrode, and platinum wire as the counter electrode, 5 wt% H 2 SO 4 The solution was used as electrolyte, the scanning speed was 5 mV / s, and cyclic voltammetry scanning was performed 8 times in the range of 0 to 1.8 V. The working electrode was taken out, washed with pure water, and dried to obtain oxygen-doped three-dimensional porous carbon EPGC.

[0040] At room temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon was used as the anode catalyst and the graphite plate was used as the cathode. -1 Na 2 SO 4 The electrolyte is the air flow rate of 5L·h -1 , at a current density of 1 mA cm -2 Under the weak electric field of , the catalytic oxidation of 1.0L of air containing 20mg·L -1 The degradation rate of p-methoxyphenol reached 100% within 2 hours.

[0041] Embodiment 4:

[0042] 2.0 g of the pretreated PGC was immersed in 60.0 g of piranha etching solution, sealed and placed in a shaker for oxidation treatment for 12 h, and then taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain OPGC; OPGC was transferred to a hydrothermal reactor and completely immersed in water. After reacting at 160 ° C for 16 h, the carbon material was taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain HPGC; finally, in a three-electrode system with HPGC as the working electrode, saturated calomel electrode as the reference electrode, and platinum wire as the counter electrode, 10 wt% H 2 SO 4 The solution was used as electrolyte, the scanning speed was 5 mV / s, and the cyclic voltammetry scanning was performed 6 times in the range of 0 to 1.8 V. The working electrode was taken out, washed with pure water, and dried to obtain the oxygen-doped three-dimensional porous carbon EPGC.

[0043] At room temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon was used as the anode catalyst and the graphite plate was used as the cathode. -1 Na 2 SO 4 The electrolyte is the air flow rate of 5L·h -1 , at a current density of 1 mA cm -2 Driven by a weak electric field, the catalytic oxidation of 1.0L of air containing 5mg·L -1 The degradation rate of phenol in simulated organic wastewater reached 100% within 2 hours.

[0044] Embodiment 5:

[0045] 2.0 g of the pretreated PGC was immersed in 80.0 g of piranha etching solution, sealed and placed in a shaker for oxidation treatment for 8 h, and then taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain OPGC; OPGC was transferred to a hydrothermal reactor and completely immersed in water. After reacting at 160 ° C for 10 h, the carbon material was taken out and washed alternately with deionized water and anhydrous ethanol three times to obtain HPGC; finally, in a three-electrode system with HPGC as the working electrode, saturated calomel electrode as the reference electrode, and platinum wire as the counter electrode, 10 wt% H 2 SO 4 The solution was used as electrolyte, the scanning speed was 5 mV / s, and the cyclic voltammetry scanning was performed 5 times in the range of 0 to 1.8 V. The working electrode was taken out, washed with pure water, and dried to obtain the oxygen-doped three-dimensional porous carbon EPGC.

[0046] At room temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon was used as the anode catalyst and the graphite plate was used as the cathode. -1 Na 2 SO 4 The electrolyte is the air flow rate of 5L·h -1 , at a current density of 1 mA cm -2 Under the weak electric field of , the catalytic oxidation of 1.0L of air containing 5mg·L -1 In the simulated organic wastewater containing p-methoxyphenol, phenol, 4-chlorophenol and bisphenol A, the degradation rate of each phenolic compound reached 100% within 2 hours.

Claims

1. An application of oxygen-doped modified three-dimensional porous carbon, characterized in that: The oxygen-doped modified three-dimensional porous carbon is used as an anode catalyst to catalyze air oxidation and degradation of phenolic organic pollutants in wastewater; The oxygen-doped modified three-dimensional porous carbon is prepared by the following method: First, the graphitized three-dimensional porous carbon surface was oxidized using piranha etching solution as an oxidant, then subjected to a hydrothermal reaction at a certain temperature to remove unstable oxygen-containing functional groups on the surface, and finally placed in a H2SO4 solution for electrochemical activation to obtain oxygen-doped modified three-dimensional porous carbon material.

2. The use according to claim 1, characterized in that: The graphitized three-dimensional porous carbon is a commercial graphitized polyacrylonitrile-based three-dimensional porous carbon with a bottom area of ​​1.0 cm 2 , a cubic column 8 cm high, with a pore volume of 7.5 cm 3 / g; The graphitized three-dimensional porous carbon was pretreated before use, specifically, ultrasonically cleaned with acetone and ethanol respectively, and then immersed in a 2 mol / L NaOH solution at 60° C. for 12 hours.

3. The use according to claim 1, characterized in that: During the oxidation treatment, the amount of the piranha etching solution is 20 to 50 times the mass of the graphitized three-dimensional porous carbon, and the immersion oxidation time is 4 to 14 hours.

4. The use according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction is 140-220° C., and the reaction time is 6-18 hours.

5. The use according to claim 1, characterized in that: The electrochemical activation adopts cyclic voltammetry scanning method, adopts a three-electrode system, uses the carbon material after hydrothermal treatment as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum wire as the counter electrode, the scanning range is between 0 and 1.8 V, and the number of scans is 2 to 8 times; the mass fraction of the H2SO4 solution is 5 to 20wt%.

6. The use according to claim 1, characterized in that: At room temperature and pressure, in an electrolytic cell with a gas distributor at the bottom, the prepared oxygen-doped three-dimensional porous carbon was used as the anode catalyst, the graphite plate was used as the cathode, and the Na2SO4 solution was used as the electrolyte. 2 Driven by external direct current and catalytic air oxidation under certain pH conditions, phenolic organic pollutants in wastewater are degraded.

7. The use according to claim 6, characterized in that: The phenolic organic pollutant is a mixture of one or more of bisphenol A, 4-chlorophenol, phenol, and p-methoxyphenol, and the concentration of the phenolic organic pollutant is 5-20 mg / L.

8. The use according to claim 6, characterized in that: The pH value of the system was adjusted to 5~11.

9. The use according to claim 6, characterized in that: The air flow rate is 5 L / h.

Citation Information

Patent Citations

  • Electrode for electrochemical capacitor and manufacturing method therefor

    JP2014107361A